The efficacy and safety of Fuzheng traditional Chinese medicine injections in the treatment of acute ischemic stroke: a systematic review and network meta-analysis - Ren, Qiaosheng; Guo, Linlin; Zhang, Peichi; Wu, Xuefeng; Xu, Yingzhi; Cao, Kegang (Frontiers in Pharmacology, 2025)
ObjectiveThe primary objective of this network meta-analysis (NMA) was to compare and rank the relative efficacy and safety of seven distinct Fuzheng traditional Chinese medicine injections (TCMIs) combined with conventional treatment (CT), against CT, for the management of acute ischemic stroke (AIS). The overarching hypothesis was that although TCMIs + CT as a class provides benefit over CT alone, their therapeutic profiles differ.MethodsThe Cochrane Library, Embase, PubMed, Web of science, CNKI, Wanfang, VIP, and SinoMed were comprehensively searched from their inception to 11 January 2025, for randomized controlled trials (RCTs) focusing on the use of Fuzheng TCMIs + CT to treat AIS. The quality of the included RCTs was assessed using the risk-of-bias 2 (RoB2) tool. NMA in the frequentist framework was designed to access the efficacy of different Fuzheng TCMIs.ResultsA total of 70 RCTs involving 6,227 patients were enrolled. The study showed that Mailuoning injection (MLN), Huangqi injection (HQ), Shengmai injection (SHM), Ciwujia injection (CWJ), Shenfu injection (SF), and Shenmai injection (SM) combined with CT significantly improved performance compared with CT alone in treating AIS. In terms of the increase in the clinical efficacy rate, MLN + CT was most likely to be the best course of action, as was CWJ + CT in terms of the National Institute of Health Stroke Scale Score (NIHSS), Barthel Index (BI), blood lipids, the low-cut viscosity of whole blood (LCV), and interleukin-6 (IL-6). CWJ + CT was associated with the lowest rate of adverse reactions (ADRs) although the evidence base for safety comparisons remains limited. Additionally, MLN + CT was most likely to be the best treatment in terms of plasma viscosity (PV), fibrinogen (FIB) and modified Rankin Scale (mRS). Given that SF + CT ameliorated the activities of daily living (ADL) rating and C-reactive protein (CRP) level, it was most likely to be the best course of action. The treatment that was most likely to be the best in terms of the high-cut viscosity of whole blood (HCV) was SHM + CT. Considering the decrease in the tumor necrosis factor-α (TNF-α) level, SM + CT had the best chance of being the best treatment.ConclusionThe combination of CT and TCMIs had a more beneficial impact on the treatment of AIS. Both CWJ + CT and MLN + CT performed best. However, these findings should be interpreted with caution due to the methodological limitations of the included trials. Therefore, to substantiate the findings, more excellent research is required.Systematic Review RegistrationCRD42025614168.